Innovation Of Cooperative Learning Type Think Pair Share In Fiqh Subject At MA Ma’arif Sukorejo - Nur Hidayah, Reissa Arifa; Yusuf, Wiwin Fachrudin (-, 2025)
This study aims to activate the effectiveness of the Think Pair Share (TPS) cooperative learning model in improving student learning outcomes in the Fiqh subject at MA Ma'arif Sukorejo. The background of this study is based on the low level of active participation of students in the learning process, especially in the Fiqh subject which is often considered abstract and difficult to understand. The TPS model is proposed as an innovative alternative to create a more interactive, collaborative, and enjoyable learning atmosphere. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the application of the TPS model can increase student involvement in discussions, build critical thinking and collaboration skills, and strengthen students' understanding of Fiqh concepts. This method has also been shown to increase student motivation and attendance. However, there are several limitations, such as limited implementation time and the dominance of certain students in discussion groups. Overall, the TPS model is considered effective in improving the quality of Fiqh learning and is recommended as a teaching strategy that can be widely applied in Islamic religious education.